The G20 and inefficient energy subsidies: Grasping the cause of price distortions by the roots? - Tobias Belschner; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2011)
Given that energy subsidies impede the shift from conventional fuels to a more sustainable energy system, the G20's 2009 decision to reduce subsidies on fossil fuels represented an important move. Where the process will lead is still unclear. The G20 states cannot even agree on how to define subsidies, and significant resistance in the individual countries means that progress is unlikely to go any further than pre-existing national plans. But in order to meet climate protection targets, fight fuel poverty and promote a sustainable, efficient and safe energy supply, it is necessary to move towards a low-carbon energy system. Not to mention the drain on state budgets that such subsidies represent. At the moment the process has become bogged down at the interministerial level. A push from the heads of state and government is urgently needed to get the process moving again
Keywords: 320